2015
DOI: 10.1080/15548627.2015.1089374
|View full text |Cite
|
Sign up to set email alerts
|

Common γ-chain cytokine signaling is required for macroautophagy induction during CD4+ T-cell activation

Abstract: Abbreviations: ATG, autophagy-related; IFN, interferon; IL, interleukin; JAK, Janus kinase; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; MTOR, mechanistic target of rapamycin (serine/threonine kinase); NL, ammonium chloride and leupeptin; PtdIns3K, class-III phosphatidylinositol 3-kinase; RPS6KB/p70S6K, ribosomal protein S6 kinase; 70kDa STAT, signal transducer and activator of transcription; TCR, T cell receptor; T H , T helper cell; Vb, vinblastineMacroautophagy is a cellular process that med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
87
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 66 publications
6
87
1
Order By: Relevance
“…In fact, knocking down JNK1 or JNK2 in Th1 cells has been shown to reduce the number of LC3‐positive vesicles . In line with these results, at least two proteins that form part of the PI3KC3 complex are required for LC3 conjugation in CD4 + T cells: Vps34‐ as well as Beclin1‐deficient T cells show reduced macroautophagy activity following TCR and CD28 stimulation .…”
Section: Regulation Of Macroautophagy In T Cellssupporting
confidence: 55%
See 4 more Smart Citations
“…In fact, knocking down JNK1 or JNK2 in Th1 cells has been shown to reduce the number of LC3‐positive vesicles . In line with these results, at least two proteins that form part of the PI3KC3 complex are required for LC3 conjugation in CD4 + T cells: Vps34‐ as well as Beclin1‐deficient T cells show reduced macroautophagy activity following TCR and CD28 stimulation .…”
Section: Regulation Of Macroautophagy In T Cellssupporting
confidence: 55%
“…Several studies have shown that TCR engagement in CD4 + and CD8 + T cells induces macroautophagy . Full activation of T cells requires TCR engagement together with costimulatory molecules and cytokine signaling.…”
Section: Regulation Of Macroautophagy In T Cellsmentioning
confidence: 99%
See 3 more Smart Citations